The synergistic effect of Levilactobacillus brevis IBRC-M10790 and vitamin D3 on Helicobacter pylori-induced inflammation - Nabavi-Rad, Ali; Jamshidizadeh, Shaghayegh; Azizi, Mahsa; Yadegar, Abbas; Robinson, Karen; Monaghan, Tanya M.; Zali, Mohammad Reza (Frontiers in Cellular and Infection Microbiology, 2023)
Owing to the emergence and spread of multidrug resistance mechanisms in Helicobacter pylori, achieving a successful eradication has become exceedingly difficult. Thus, this study for the first time determines the effect of a combination of vitamin D3 and probiotic on the pathogenesis and treatment of H. pylori. We established an in vitro experimental system using AGS human gastric carcinoma cells and explored the synergistic effect of Levilactobacillus brevis IBRC-M10790 and vitamin D3 on H. pylori. Live and pasteurized L. brevis, L. brevis-derived membrane vesicles (MVs), and L. brevis cell free supernatant (CFS), as well as their combination with vitamin D3 were used during this study. We assessed the anti-inflammatory and anti-oxidative effects of these combinations using RT-qPCR and ELISA, respectively. We further performed an adhesion assay to evaluate the influence of L. brevis and vitamin D3 on the adherence rate of H. pylori to AGS cells. Our results demonstrated that L. brevis and vitamin D3 possess anti-inflammatory and anti-oxidative effects against H. pylori infection in AGS cells. The combination of vitamin D3 with the probiotic strain (particularly live L. brevis and its CFS) can more efficiently reduce the expression of pro-inflammatory cytokines IL-6, IL-8, IFN-γ, and TNF-α in the AGS cells. Moreover, vitamin D3 and L. brevis exhibited an additive impact preserving the integrity of the epithelial barrier by increasing the expression of the tight junction protein ZO-1. Furthermore, this combination can potentially reduce H. pylori adherence to AGS cells. This study indicates the advantage of combining vitamin D3 and probiotic to attenuate H. pylori-induced inflammation and oxidative stress. Consequently, probiotic and vitamin D3 co-supplementation can be considered as a novel therapeutic approach to manage and prevent H. pylori infection.